Bilateral choroid plexus resection in a 9p hexasomy/tetrasomy mosaic patient - Rei Takada; Takenori Tozawa; Takumi Yamanaka; Masaharu Moroto; Tomoko Iehara; Tomohiro Chiyonobu (Human Genome Variation)
Abstract Previous reports have shown that a gain of the chromosome 9 short arm (9p) is associated with choroid plexus hyperplasia (CPH). Furthermore, CPH can lead to communicating hydrocephalus; however, no cases of CPH with 9p gain requiring choroid plexus resection have been reported. Here, we describe the first case in which a 9p hexasomy/tetrasomy mosaic patient required choroid plexus resection for hydrocephalus. This finding suggested that the 9p copy number is correlated with CPH severity.